Análise do preparo de canais radiculares realizado pelos alunos do curso de odontologia da UFES utilizando-se a diafanização - De Martin, Georje (2013)
The first contact of students with Endodontics Dentistry School of the Federal University of Espírito Santo is in the fifth period of the course in the Discipline of Endodontics I. In it, students know the Endodontics principles: morphology, coronary access, root canal preparation techniques, disinfection and obturation of the root canal system. Learning occurs in previously extracted teeth before the academics have any contact with the endodontic clinic at the Discipline of Endodontics II in the following period. The aim of this study was to analyze through the clearing technique the canals were prepared during this Discipline (laboratory). The quality of the preparation chemical-mechanical techniques was examined concern the shaping of the root canal and compared the best result of the same, visualized the anatomical features of the root canal system, compared the radiographic exam of the teeth and clearing technique and also checked whether the students have assimilated the knowledge of Endodontics. The data collected were subjected to Binomial test,Kappa and Chi-square test. These showed that: the modeling of root canals analyzed by the clearing technique, 67% were modeled with a statistical significance of 0.002 (p<0.05), as the comparison between the preparation chemical-mechanical techniques used in relation to the relative frequency the variable modeling of the root canals was 65.9% when modeled channels prepared with step-back technique and 68.2% of teeth modeled when prepared by Oregon Modified technique (p=0.8206) with no statistically significant difference between techniques, and as the concordance of the results of variable modeling of the root canals between the radiographic examination (73.8%) and clearing technique (67%) yielded a Kappa value=0.511 showing a moderate agreement between the two visualization techniques. It was concluded that: the modeling of channels was satisfactory showing that students are assimilating the knowledge of the Discipline; radiography proved to be limited in view of the channel modeling and also in view of the anatomical features of the root canal system, and also that the clearing technique is a visualization technique accessible and essential to the development of education in the Discipline of Endodontics.